Spare tire? Stock markets, banking crises, and economic recoveries - Levine, Ross; Lin, Chen; Xie, Wensi (Journal of Financial Economics, 2016)
Do stock markets act as a spare tire during banking crises, providing an alternative corporate financing channel and mitigating the economic severity of these crises? Using firm-level data in 36 countries from 1990 through 2011, we find that the adverse consequences of banking crises on equity issuances, firm profitability, employment, and investment efficiency are smaller in countries with stronger shareholder protection laws. These findings are not explained by the development of stock markets or financial institutions prior to the crises, the severity of the banking crisis, or overall economic, legal, and institutional development.